Phenotyping of Rh, Kell, Duffy and Kidd blood group antigens among non-tribal and tribal population of South Gujarat and its implication in preventing alloimmunisations in multitransfused patients. - Avani Shah; Kanjaksha Ghosh; Preeti Sharma; Kanchan Mishra (Mediterranean Journal of Hematology and Infectious Diseases)
Background:Sickle cell anaemia is common amongst Tribal population of south Gujrat. Alloimmunisation in multitransfused sickle cell anaemia patient is 10 times commoner in these patients than beta Thalassemia  major  patients from regular blood donor communities.